A comparative analysis of survival outcomes between pancreatectomy and chemotherapy for elderly patients with adenocarcinoma of the pancreas. Issue 21 (15th July 2016) - Marmor, Schelomo; Burke, Erin E.; Virnig, Beth A.; Jensen, Eric H.; Tuttle, Todd M.
Abstract : BACKGROUND: The survival rates after pancreatectomy for elderly patients with adenocarcinoma of the pancreas remain poor. Elderly patients have increased perioperative mortality rates, higher morbidity rates, and higher rates of continued inpatient nursing care after pancreatectomy. The objective of the current study was to evaluate the outcomes of surgical resection versus chemotherapy (with or without radiotherapy) for elderly patients with potentially resectable adenocarcinoma of the pancreas. METHODS: Using Surveillance, Epidemiology, and End Results (SEER)‐Medicare data for 2000 through 2010, the authors examined the relationship between patient characteristics and receipt of surgery using multivariate logistic regression. The patient cohort was restricted to patients with American Joint Committee on Cancer stage I and stage II disease and Charlson Comorbidity index of ≤2. The association between treatment (surgery or chemotherapy without surgery) and hazard of death was evaluated using Kaplan‐Meier Cox proportional hazards modeling. RESULTS: The authors identified 2629 patients with pancreatic adenocarcinoma who underwent either surgery (pancreatectomy) or chemotherapy without surgery. Younger patient age and smaller tumor size were found to be significantly associated with receipt of surgery. For the overall cohort, the median survival rate was significantly longer for those patients treated with surgery compared with those who received chemotherapy (15 months vs 10 months). However, the absolute survival benefit attenuated as the cohort became older. CONCLUSIONS: The survival benefit associated with surgical resection compared with chemotherapy was very small for certain subgroups of patients (those aged ≥80 years and those with lymph node metastases). The results of the current study indicate that although surgery is associated with a survival benefit in the elderly, chemotherapy should be considered as a legitimate therapeutic alternative. Cancer 2016 . © 2016 American Cancer Society . Cancer 2016;122:3378–3385 . © 2016 American Cancer Society . Abstract : In the current study, survival rates after either surgery or chemotherapy alone are compared among elderly patients with pancreatic cancer. For the entire patient cohort, surgical treatment appears to be associated with improved survival rates, but the absolute benefit of surgery appears minimal for certain groups of patients (those aged ≥80 years and those with lymph node metastases).